Optimal structural design for offshore wind energy system - Chew, Kok Hon (2017)
Offshore wind industry has been gaining much momentum over the last decade due to increasing energy demand and global appeal to create a balanced energy mix. Current wind energy research and development has been focusing on driving down the cost of energy. Support structures of offshore wind turbines are site-specifically designed and can be optimized for cost reduction. However, the task is computationally expensive due to the highly-constrained, non-convex and non-linear nature of the design problem. A good depth of detail in the problem formulation can give useful insights in the practical design process, but may also compromise the efficiency. Therefore, the main objective of this thesis is to investigate an efficient, effective and practical automated structural optimization framework for designing the support structures of offshore wind turbines, where efficiency relates to the convergence speed to attain the optimal design; effectiveness measures the degree of success to converge to the correct optimal solution reliably and practicality represents the quality of a design problem being mathematically formulated to fit to the industrial requirements.